ASSESSING THE ROLE OF EDUCATION IN ADULT WOMEN'S KNOWLEDGE AND AWARENESS OF HUMAN PAPILLOMAVIRUS AND HUMAN PAPILLOMAVIRUS VACCINE - Ismail, Humera; Rafiq, Sarah; Shakoor, Shafia; Karim, Muhammad Tariq; Raheel, Rabia (Journal of Ayub Medical College Abbottabad, 2017)
Background: Awareness and knowledge of Human Papillomavirus (HPV) and HPV vaccine among women are not satisfactory in developing countries. The aim of this study was to assess the role of education in adult women about knowledge and awareness of human papillomavirus (HPV) and HPV vaccine. Methods: This cross-sectional study was carried out in women aged 19-50 years attending the out-patient waiting area of a tertiary care hospital in Karachi from August 2014 to August 2015. Convenience sampling was applied. After their written consent, a self-administered questionnaire was used to obtain information regarding role of education and awareness, knowledge of human papillomavirus (HPV) and HPV vaccine. A total of 600 women completed the questionnaire. Results: Mean age of the study participants was 39±10.7 years. About 68% (n=405) had an education level intermediate or less, while 33% (n=195) had a bachelors or higher degree. A total of 56.3% (n=338) women were aged less than 40 years. Conclusion: Awareness among women varies with the level of education acquired. As shown by results, a lesser proportion of undergraduate women were aware about HPV and its related diseases as compared women at graduate level. Moreover, our study identifies significant gaps in knowledge about sexually transmitted infections, HPV, cervical cancer and its prevention. There is an urgent need to develop public awareness programs targeting the adolescent and young adult women of our country. Keywords: Human Papillomavirus (HPV); HPV vaccine; Education; Adults; Women